Children and Youth Participation: Attitudes of Children and Young People Towards Democracy - Brestnichka, Maria (Research Papers, 2023)
The attitudes of children and young people towards democracy define their participation in the social and political life, as well as their participation in the development of the public understanding of the democracy overall. Despite the fact that the children and young people between 15 and 24 are barely 10% from the Bulgarian population, their participation has a key influence on the national progress and the political processes. In the past years a low level of interest and participation in the democratic processes of the lower age groups is observed. This is the focus of the research, which uses data from the 10th edition of the European Social Survey for Bulgaria.